Vesico-urethral anastomotic stenosis following radical prostatectomy: a multi-institutional outcome analysis with a focus on endoscopic approach, surgical sequence, and the impact of radiation therapy - Pfalzgraf, Daniel Philipp; Worst, Thomas; Kranz, Jennifer; Steffens, Joachim; Salomon, Georg; Fisch, Margit; Reiß, Christoph-Philip; Vetterlein, Malte Wolfram; Rosenbaum, Clemens Mathias (World journal of urology, 2021)
To investigate the predictors of recurrence and of de novo incontinence in patients treated by transurethral incision or resection for vesico-urethral anastomotic stenosis (VUAS) after radical prostatectomy.